Perancangan Aplikasi Pengumuman Kampus Berbasis Android Pada STKIP-PGRI Lubuk Linggau - Antoni Zulius (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
College of Teacher Training and Education (STKIP-PGRI) Lubuklinggau is one of the private universities in Lubuklinggau city, focusing on human resource development in teacher training and education. STKIP-PGRI Lubuklinggau currently has many students, including students who live in Lubuklinggau and others from outside the city of Lubuklinggau. Students who live far from the campus find it difficult to obtain academic-related academic information such as lecture announcement information, announcement of final semester exam schedule, announcement of exam schedule, announcement of thesis examination schedule, announcement of KRS retrieval schedule, and announcement of KHS taking schedule. As a solution of the problem of student difficulties, it must be made an application of Campus Based Announcement Application of Android on STKIP-PGRI Lubuklinggau so that students more quickly in obtaining information campus announcement STKIP-PGRI Lubuklinggau flexibly without boundaries of time and place.